Bringing Traditional Literature to Life: Implementation of Pantun Literacy among Children in Sanggar Bimbingan Ampang, Malaysia - Ahmad Fuadi; Zaifatur Ridha; Diani Syahfitri; Nurhaliza Nurhaliza; Rohil Aisyah; Nur Farah Azila (International Journal of Science Education and Cultural Studies, 2025)
Literacy pantun is a form of oral literature that not only functions as entertainment but also as an educational tool for improving children’s language skills and critical thinking. This study aims to implement pantun literacy as a learning strategy in Sanggar Bimbingan Ampang, Selangor, Malaysia, to improve the literacy skills of children of Indonesian migrant workers (TKI). The method used in this program involves a participatory approach by introducing pantun, language games, practice of pantun, and pantun competition. The program was designed so that children can learn fun while remaining rooted in Malay culture, which is rich in moral values. The results demonstrated that pantun literacy improved the children’s language skills in terms of vocabulary, sentence structure, and creative thinking. Children who were initially less interested in literacy activities began to show greater interest in reading, writing , and communicating orally through pantun. The program also increased children's confidence in public speaking and strengthened their understanding of Indonesian culture, even though they grew up in an environment with more exposure to foreign cultures. The conclusion of this activity demonstrates that pantun literacy can be an effective strategy for improving children’s literacy skills through a culture-based approach. The success of this programme will encourage the integration of pantun literacy into language-learning in education centers and formal schools. For further development, support is needed in the form of providing adequate resources, training for educators, and utilizing digital technology so that pantun literacy can continue to be preserved and utilized as an innovative and interesting learning tool.